2021
DOI: 10.3390/s21103380
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Evidential Grid Mapping Using Monocular and Stereo Cameras

Abstract: Accurately estimating the current state of local traffic scenes is one of the key problems in the development of software components for automated vehicles. In addition to details on free space and drivability, static and dynamic traffic participants and information on the semantics may also be included in the desired representation. Multi-layer grid maps allow the inclusion of all of this information in a common representation. However, most existing grid mapping approaches only process range sensor measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Currently, most of the work related to improving edge depth requires the introduction of an additional network, e.g., semantic segmentation [10][11][12], edge map detection networks [13][14][15], or optical flow [16]. We found that research on uncertainty, which has only recently entered the limelight, can also improve the quality of edge depth and without learning other complex networks.…”
Section: Introductionmentioning
confidence: 92%
“…Currently, most of the work related to improving edge depth requires the introduction of an additional network, e.g., semantic segmentation [10][11][12], edge map detection networks [13][14][15], or optical flow [16]. We found that research on uncertainty, which has only recently entered the limelight, can also improve the quality of edge depth and without learning other complex networks.…”
Section: Introductionmentioning
confidence: 92%
“…None of the above-mentioned publications models occupancy and semantic estimates in a joint evidential context. In [19]- [21] a sensor grid mapping pipeline was presented estimating a BBA on a FOD containing ground and object hypotheses for range sensors and cameras. Here, we present an advancement of the evidential model and rethink the BBA estimation.…”
Section: B Grid Mapping With Camerasmentioning
confidence: 99%
“…Since semantic landmarks are associated with Wi-Fi landmarks, Wi-Fi fingerprinting is used to determine a one-to-one association between semantic landmarks. Additionally, the distance between semantic landmarks is calculated using Equations ( 6)- (8). Utilizing pre-matching significantly improves the efficiency of matching landmarks.…”
Section: 𝑆𝑐𝑜𝑟𝑒mentioning
confidence: 99%
“…Scholars have proposed many sensor-based mapping solutions, such as lidar-based [7], camera-based [8], Wi-Fi-based, inertial measurement unit (IMU)-based, and magneticbased [9], to solve the mapping problem in unknown indoor environments. Due to these sensors' inherent characteristics, single-sensor-based map construction methods have limited application scopes.…”
Section: Introductionmentioning
confidence: 99%